Unframed : practices and politics of women's contemporary painting - Betterton, Rosemary (I.B. Tauris, 2003)
Women's painting is undergoing a vibrant revival, yet has been little explored in writing or modern visual culture. "Unframed" is an examination of women's contemporary painting. It presents writing with practitioners who engage with theory and critical theorists who deal directly with contemporary practice. All contributors reflect on their own practice and that of other women painters and theorists, whose common aim is to develop innovative ways of thinking about, and through, painting by women. The book focuses on current debates on gender, subjectivity, spectatorship and painting.